👤

aider moi s'il vous plait
montre que
∀(x,y,z)∈R³ on a
  x² - y ≠z² ⇒[tex] \sqrt{x+ \sqrt{y} } \neq \sqrt{ \frac{x+z}{2} } + \sqrt{ \frac{x-z}{2} } [/tex]


Répondre :

supposons au contraire que   rac( x +rac(y))  =rac( x+z) /2  + rac( x -z) /2   on aurait  forcement    x +rac(y) = (x+z)/2  +(x-z)+ 2 rac( x+z) /2  * rac( x -z) /2  donc   x  + rac(y) = x + rac( x+z) rac( x -z)   et    rac(y) =   rac( x+z) rac( x -z)   d'où on aurait     y = (x+z)(x-z)  = x² -z²     soit   x² - y =z²    ce qui montre l'implication